2012
DOI: 10.1080/17408989.2011.649725
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the provision of coach education: the recommendations of UK coaching practitioners

Abstract: Background: Coach education has been identified as a key vehicle for raising the standard of coaching practice. However, the existing body of literature suggests that coach education has had a limited impact on the learning and development of coaching practitioners. In this respect, it has been contended that coach educations ills might be partially attributed to the 'top-down' approach of its design and delivery. While numerous theoretically informed pedagogies have been suggested as a means of overcoming som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
131
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(146 citation statements)
references
References 31 publications
9
131
0
6
Order By: Relevance
“…The wider remit here being that coach education programmes should reduce the focus on the descriptive, tactical, technical and biosocial aspects of the sport (Piggott, 2012), and instead adopt non-linear pedagogical principles to learning (Chow et al, 2006). In effect, overcoming 'knowledge-deficits' recognising that there are widespread concerns about the education of coaches in the UK where the 'one size fits all' approach stands accused of being largely ineffective in creating a theoretically literate coaching workforce (Nelson, Cushion & Potrac, 2012;Piggott, 2015;Cushion & Hull, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The wider remit here being that coach education programmes should reduce the focus on the descriptive, tactical, technical and biosocial aspects of the sport (Piggott, 2012), and instead adopt non-linear pedagogical principles to learning (Chow et al, 2006). In effect, overcoming 'knowledge-deficits' recognising that there are widespread concerns about the education of coaches in the UK where the 'one size fits all' approach stands accused of being largely ineffective in creating a theoretically literate coaching workforce (Nelson, Cushion & Potrac, 2012;Piggott, 2015;Cushion & Hull, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The impact of coach education has received significant attention from the academic community in recent years (for example see: Cushion & Hull, 2013;Nelson, Cushion & Potrac, 2012; Piggott, 2015; Cushion, Armour & Jones, 2003;Mallett, Trudel, Lyle & Rynne, 2009; Bush, Silk, Andrews & Lauder, 2013). Multiple criticisms have come to the fore, but in the main, it has been noted that attempts to provide sufficient learning opportunities in large scale coaching programmes through accumulating hours in practice, is at best considered dated (Piggott, 2012; Morgan, Jones, Gilbourne & Llewellyn, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stakeholder 11 agreed that cost was important, saying, "I find it difficult when, if we make it compulsory for a coach to be part of, that they have to pay it themselves." Findings from the coaching-related research field have shown that cost deters coaches from engaging with education opportunities, particularly if the coaches do not highly value the content (Nelson, Cushion, & Potrac, 2013). As a potential solution, a number of stakeholders viewed developing their own programme as more cost-effective.…”
Section: Lack Of Resourcementioning
confidence: 99%
“…Such findings are echoed with amateur coaches in Canada (Lemyre et al 2007) and Portugal (Mesquita et al 2010) and are further supported by a common posture in the literature that dismisses formal learning as rigid, out-dated and largely irrelevant to coach development (cf. Cassidy et al 2006;Roberts 2010;Chesterfield et al 2010;Nash and Sproule 2011;Nelson et al 2012). …”
Section: Coach Learningmentioning
confidence: 99%